Heavenly Sustenance in Patristic Texts and Byzantine Iconography Nourished by the Word - Ene D-Vasilescu, Elena (New Approaches to Byzantine History and Culture, 2018)
This book examines ideas of spiritual nourishment as maintained chiefly by Patristic theologians -those who lived in Byzantium. It shows how a particular type of Byzantine frescoes and icons illustrated the views of Patristic thinkers on the connections between the heavenly and the earthly worlds. The author explores the occurrence, and geographical distribution, of this new type of iconography that manifested itself in representations concerned with the human body, and argues that these were a reaction to docetist ideas. The volume also investigates the diffusion of saints' cults and demonstrates that this took place on a North-South axis as their veneration began in Byzantium and gradually reached the northern part of Europe, and eventually the entirety of Christendom. .